2005
DOI: 10.4028/www.scientific.net/msf.495-497.447
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Relationship during Partial α-γ-Phase Transformation in Microalloyed Steels

Abstract: The ferrite to austenite phase transformation in microalloyed steel was studied, with a special focus on the orientation relationship between prior ferrite and subsequent austenite. Also the role of growth selection and preferred nucleation was investigated in this context. Their effects were examined at partial phase transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
2
8
0
Order By: Relevance
“…The K-S relationship and the Nishiyama relationship 26) are also shown in the same notation. Many of the α/γ interfaces have an orientation relationship quite close to the K-S relationship, that is, the orientation relationship with a misorientation of less than 2 in Δθ cpp and less than 2 in Δθ cpd is held at 16% of all the interfaces 19,27) . These orientation relationships are satis ed at Interface 1.…”
Section: (B) and (C)mentioning
confidence: 99%
See 2 more Smart Citations
“…The K-S relationship and the Nishiyama relationship 26) are also shown in the same notation. Many of the α/γ interfaces have an orientation relationship quite close to the K-S relationship, that is, the orientation relationship with a misorientation of less than 2 in Δθ cpp and less than 2 in Δθ cpd is held at 16% of all the interfaces 19,27) . These orientation relationships are satis ed at Interface 1.…”
Section: (B) and (C)mentioning
confidence: 99%
“…Concerning the model of the double K-S relationship, Lischewski et al observed the α→γ phase transformation of a C-Mn steel containing micro-alloying elements by in situ electron back-scattering diffraction (EBSD) measurement, and analyzed the orientation relationship between the parent α and the transformed γ 19,20) . A considerable number of transformed γ grains satisfy the multiple K-S relationship with adjacent α grains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10) Lischewski et al observed the α→γ phase transformation in a C-Mn steel containing microalloying elements by in situ electron backscattering diffraction (EBSD) measurement and analyzed the orientation relationship between the parent ferrite grains and transformed austenite grains at triple junction. 17,18) They found that a considerable number of transformed austenite grains are related to two adjacent mother grains by the approximate K-S relationship and deduced that the reason for such a variant selection is due to the preferential nucleation of the K-S variant with low interfacial energy.…”
Section: Introductionmentioning
confidence: 99%
“…The variant selection of austenite during reverse transformation has been discussed in the literatures and several models have been proposed. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Tomida et al proposed the variant selection model to predict the texture change in α→γ transformation based on the orientation relationships at multiple interfaces with different ferrite grains. 9,10) In these studies, the variant of austenite is assumed to be selected to simultaneously satisfy the Kurdjumov-Sachs (K-S) relationship 20) with one ferrite grain and an orientation relationship near the K-S relationship with about 10° of the tolerance angle with other adjoining ferrite grains.…”
Section: Introductionmentioning
confidence: 99%